Commissioning, clinical implementation, and performance of the Mobetron 2000 for intraoperative radiation therapy. (January 2017) - Wootton, Landon S.; Meyer, Juergen; Kim, Edward; Phillips, Mark
Abstract: The Mobetron is a mobile electron accelerator designed to deliver therapeutic radiation dose intraoperatively while diseased tissue is exposed. Experience with the Mobetron 1000 has been reported extensively. However, since the time of those publications a new model, the Mobetron 2000, has become commercially available. Experience commissioning this new model and 3 years of data from historical use are reported here. Descriptions of differences between the models are emphasized, both in physical form and in dosimetric characteristics. Results from commissioning measurements including output factors, air gap factors, percent depth doses (PDDs), and 2D dose profiles are reported. Output factors are found to have changed considerably in the new model, with factors as high as 1.7 being measured. An example lookup table of appropriate accessory/energy combinations for a given target dimension is presented, and the method used to generate it described. Results from 3 years of daily QA measurements are outlined. Finally, practical considerations garnered from 3 years of use are presented.